Analisis Dampak Body Shaming pada Remaja Perempuan Awal di SMP Negeri 213 Jakarta - Damayanti Damayanti; Desy Safitri; Abdul Haris Fatgehipon (SOSIAL : Jurnal Ilmiah Pendidikan IPS, 2025)
This research was motivated by the rising number of adolescent girls experiencing body shaming, which can lead to negative consequences, particularly affecting their self-confidence. The aim of this study is to explore the impacts felt by female junior high school students after experiencing body shaming. A descriptive method was employed, using questionnaires, interviews, and documentation as data collection techniques. The population of this study consisted of 144 eighth-grade female students at SMP Negeri 213 Jakarta in the 2024/2025 academic year. The sample was selected through purposive sampling, with a total of 50 participants. The data were analyzed using descriptive analysis techniques. The results of the study show that: 1) Body shaming has a significant impact on the four analyzed aspects: global subjective satisfaction, affective distress regarding appearance, cognitive aspects of body image, and behavioral aspects of body shaming. Each aspect shows a negative influence, although the intensity varies. 2) In this study, the cognitive aspect was identified as the most dominant impact, with 38% of respondents categorized as experiencing a high level.